AMBASSADORIAL SERVICE AND INTERNATIONAL AGREEMENTS - Madaminov Tuqinjon Mamayunusovich; Mirzaliyeva Zarina Jahongir qizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
In this article, the diplomatic relations of the Italian state with various countries in the Middle Ages and their importance in the development of the country are fully explained.